Role of the bitter taste receptor T2R38 in upper respiratory infection and chronic rhinosinusitis. Issue 1 (February 2015) - Lee, Robert J.; Cohen, Noam A.
<x xml:space="preserve">Abstract</x> Purpose of review Taste receptor family 2 (T2R) bitter taste receptors were originally identified and named on the basis of their role in type 2 taste cells of the tongue, in which they serve to detect the presence of potentially harmful ingested chemicals. In 2009, researchers demonstrated that airway epithelial cells also express T2R receptors, but their role in airway physiology and human disease has only recently begun to be identified. Recent findings Recent research has demonstrated that at least one airway T2R receptor, taste receptor family 2 isoform 38 protein (T2R38) is activated by secreted bacterial products. Activation of T2R38 in sinonasal epithelial cells stimulates nitric oxide production, increasing ciliary beating and directly killing bacteria. Clinical studies have also found correlations of TAS2R38 genotype with susceptibility to gram-negative upper respiratory infection and established T2R38 as an independent risk factor for chronic rhinosinusitis requiring sinus surgery. Summary These recent studies identify a role for T2R38 in sinonasal innate immunity and chronic rhinosinusitis. Clinical implications include the potential development of T2R38-directed topical therapies, as well as using taste testing and/or genotyping to predict susceptibility to infection. Further studies are needed to more clearly determine how TAS2R38 genotype affects patient outcomes in chronic rhinosinusitis and other upper airway diseases.